Heat basis of construction of lead battery grid continuous casting machines - E. F. Baranovsky; V. M. Iljushenko; V. A. Pumpur; A. I. Kalentionok (Литьë и металлургия, 2001)
Heat exchange during continuos casting of a lead battery greed is investigated. Thermal analysis of mold design values and of melting furnace electric power of the continuos casting machine is made.